Dealing with inquiry-based teaching in science - Kamarudin, Nurzatulshima; Phang, Yeen Cheng; Lee, Tze Jiun (2015)
Science education aims to prepare students to display their scientific skills, knowledge or ability and their proficiency as a scientist. The teaching and learning of science should be not about regurgitating meanings and evidences given by the science teacher. Therefore, this paper explores and deals with inquiry-based teaching in science. There are four types of inquiry-based teaching approaches depending on the learners’ condition, namely confirmation inquiry, structured inquiry, guided inquiry and open inquiry. The use of inquiry-based teaching in science involves several stages and brings numerous benefits. However, there are several challenges encountered when implementing inquiry in teaching science. Managing inquiry teaching in the science classroom can be demanding. Nowadays, teachers and students must share equal responsibility in learning. Students need to develop inquiry skills so that they can handle different circumstances and move towards being lifelong learners.